2021
DOI: 10.5194/bg-18-5595-2021
|View full text |Cite
|
Sign up to set email alerts
|

Grazing behavior and winter phytoplankton accumulation

Abstract: Abstract. Recent observations have shown that phytoplankton biomass increases in the North Atlantic during winter, even when the mixed layer is deepening and light is limited. Current theories suggest that this is due to a release from grazing pressure. Here we demonstrate that the often-used grazing models that are linear at low phytoplankton concentration do not allow for a wintertime increase in phytoplankton biomass. However, mathematical formulations of grazing as a function of phytoplankton concentration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…In addition, following Freilich et al. (2021), the deepening MLD dilutes the volume concentration through wintertime (Equation ). Whereas when MLD shallows in the growing season, material detrained, but the volumetric concentration in the mixed layer will remain almost unchanged.…”
Section: The Ross Ice Shelf Polynya Ecosystem Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, following Freilich et al. (2021), the deepening MLD dilutes the volume concentration through wintertime (Equation ). Whereas when MLD shallows in the growing season, material detrained, but the volumetric concentration in the mixed layer will remain almost unchanged.…”
Section: The Ross Ice Shelf Polynya Ecosystem Modelmentioning
confidence: 96%
“…In Equation 16, the shear rate (sh) is set to 0.8 s −1 and the value of the minimum sinking rate of phytoplankton ( 𝐴𝐴 𝐴𝐴 B ) is presented in Table 2. In addition, following Freilich et al (2021), the deepening MLD dilutes the volume concentration through wintertime (Equation 17). Whereas when MLD shallows in the growing season, material detrained, but the volumetric concentration in the mixed layer will remain almost unchanged.…”
Section: Fementioning
confidence: 99%
“…We do not explicitly represent the grazing by zooplankton. Instead, we consider nutrient limitation and a quadratic loss term which increases the mortality to account for phytoplankton biomass losses due to higher-trophic level predation (Freilich et al, 2021) and to enhance the phytoplankton response to sporadic nutrient uptake (Freilich and Mahadevan, 2019). Lastly, the ammonium is initialized as zero.…”
Section: P Zmentioning
confidence: 99%
“…In particular, the dynamics of small phytoplankton (< 10 µm) are tightly coupled with those of microzooplankton grazers due to their fast ingestion and growth rates (Hansen et al, 1997;Haraguchi et al, 2018), allowing them to consume most phytoplankton primary production in the ocean, including coastal habitats (Calbet and Landry, 2004). Also, a Holling III functional response seems to best describe the grazing behavior of microzooplankton (Liu et al, 2021), which might be key at low winter food concentrations to allow phytoplankton biomass to accumulate (Freilich et al, 2021). At Stonehaven, we observed that small phytoplankton dominated the winter community biomass, as also occurs in other temperate oceanic and coastal areas (see for instance Haraguchi et al, 2018;Bolaños et al, 2020).…”
Section: Effect Of Light On the Spring Bloom Onsetmentioning
confidence: 99%